Effect of Macro-element Deficiencies on Fresh and Dry Mattbr, Mineral Uptake and Holocellulose Production by Pinus garibaea Seedlings - Talwar, K. K.; Bratnagar, H. P. (Indian Forester, 1979)
Pot culture experiments were conducted with the seedings of Pinus Garibaea to evaluate the influence of deficiencies of macro-elements on dry matter and holocellulose production and mineral uptake. Deficiencies of all the macro-elements have reduced dry matter production. Lowest dry matter was produced in potassium deficiency treatment. Plant analysis results. have indicated that different deficiency treatments influence mineral uptakte differently. Holocellulose productions has shOwn direct linear relation to shoot dry weight.